Heart rhythm disorders and features of their management at COVID-19 pandemic - Yu.M. Mostovoy; T.D. Danilevych (Кардіохірургія та інтервенційна кардіологія)
COVID-19 infection spread rapidly around the world and reached the level of a pandemic, leading to significant morbidity, healthcare tension, increased mortality, economic instability and social problems. The severe course of coronavirus infection quite often leads to cardiovascular complications. Among them, the most common are myocarditis, cardiomyopathies, myocardial infarction, pulmonary embolism and cardiac arrhythmias. The exact mechanisms of cardiovascular complications are currently unknown, but their search is underway. Patients with pre-existing cardiovascular disease and risk factors are more likely to experience adverse effects associated with COVID-19. In addition, there are data about the first appearing heart problems. Probable mechanisms of their occurrence are: direct viral invasion of cardiomyocytes, hypoxia, systemic inflammatory reaction, cytokine "storm" (increased levels of ferritin, lactate dehydrogenase, C-reactive protein, interleukin-6, catecholamines), myocardial ischemia, electrolyte imbalance, volume overload, hypercoagulation, proarrhythmogenic side effects of drugs, etc. In turn, it is quite interesting, both from a scientific and practical point of view, to study the features of the prevalence and structure of arrhythmias at COVID-19 among the population of Ukraine. In addition, there are controversial questions about the features of their management, drug interactions, routing and prognosis of the patients. The review displays the latest data from both foreign and domestic scientists about the prevalence of rhythm disorders against the background of coronavirus infection and highlights the main problematic issues of the management of the patients